Development of Aptamer-Coated Beads for PDGF-BB Capture - Sangkeaw, Pimchanok; Saengkaew, Jittraporn; Soontornworajit, Boonchoy (Thai Journal of Science and Technology, 2017)
Abstract Nowadays, proteins play significant role in the advance of human well-being due to their molecular functions. Therefore, several attentions have been drawn to improve protein production including purification process. This research aimed to improve a protein purification tool for platelet-derived growth factor BB (PDGF-BB) by developing aptamer coated polystyrene beads. The aptamer was a binding site for the proteins. The aptamer was immobilized onto the beads via amide bond couplingstrategy that performed by using EDC. The aptamer immobilization was confirmed by flow cytometry. The effects of EDC, aptamer concentration, and acidic/basic condition on the coupling efficiency were studied. For the EDC-based coupling, the results showed that the coupling reaction increased its efficacy at high concentration of those reagents under acidic condition. After the immobilization, the capturing ability of aptamer-coated beads to PDGF-BB was tested. The amount of PDGF-BB that has been captured by the particles and eluted by complementary oligonucleotide was determined by ELISA. Results demonstrated that the aptamer-coated beads were able to capture PDGF-BB. However, the PDGF-BB elution by complementary oligonucleotide was not successful. It suggested that an elution process needed further improvements. Keywords: PDGF-BB; aptamer; amide coupling; polystyrene beads; protein purification